2022
DOI: 10.1371/journal.pmed.1003959
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HIV treatment outcomes with reduced frequency of clinical encounters and antiretroviral treatment refills: A systematic review and meta-analysis

Abstract: Background Global HIV treatment programs have sought to lengthen the interval between clinical encounters for people living with HIV (PLWH) who are established on antiretroviral treatment (ART) to reduce the burden of seeking care and to decongest health facilities. The overall effect of reduced visit frequency on HIV treatment outcomes is however unknown. We conducted a systematic review and meta-analysis to evaluate the effect of implementation strategies that reduce the frequency of clinical appointments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…Our findings are consistent with those from existing research, although data are lacking. A recent systematic review compared clinical outcomes among PLHIV with reduced (6-to 12-monthly) clinical consultations to those among PLHIV with 3-monthly clinical visits [9]. All studies included in the review analysed PLHIV who were established on ART, and most utilised clinical outcomes with a 12-month duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with those from existing research, although data are lacking. A recent systematic review compared clinical outcomes among PLHIV with reduced (6-to 12-monthly) clinical consultations to those among PLHIV with 3-monthly clinical visits [9]. All studies included in the review analysed PLHIV who were established on ART, and most utilised clinical outcomes with a 12-month duration.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the impact of extended ART prescriptions on clinical outcomes among PLHIV who are established on treatment [9]. Therefore, in this study we use data from a large community-based DSD programme in South Africa to investigate whether clinical outcomes among PLHIV given 12-month ART prescriptions differed from those given 6-month prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…In recognition of an increasingly diverse set of needs for the millions of people living with HIV (PWH) on antiretroviral therapy (ART), in 2016 the WHO recommended implementation of differentiated service delivery (DSD) models [ 1 ]. Such approaches are feasible, acceptable, and achieve equivalent or improved retention in care and viral suppression compared to standard treatment [ 2 7 ]. Many countries have adopted facility-based DSD models allowing PWH established on ART to be seen less frequently for clinical assessments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With the scale-up of antiretroviral therapy (ART) with fewer side effects, many people living with HIV in countries with mature HIV programs are established on treatment and require fewer interactions with the healthcare system. DSD for HIV treatment services may encompass various strategies, including multimonth dispensing (MMD), increased time between clinic visits, fast-track ART refills, task-shifting from physicians to other types of health providers, and community ART distribution [4][5][6][7]. For clients, DSD reduces the financial burden of transportation and the time spent traveling to/from the health facility and waiting for appointments.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found 39 studies on ART refill frequency published between 2018 and 2019 [11]; however, only one of the studies was conducted in Kenya, and this study did not evaluate the facility-based, fast-track model, which includes ≥3MMD. Similarly, a systematic review examining the effect of reduced frequency of clinical encounters and antiretroviral drug refills on retention and viral load included only one study from Kenya, which included a randomized trial [7]. Whereas most DSD research to date has focused on clinical outcomes, little is known about individual and facility-level factors associated with being on at least 3MMD among eligible clients and switching out from ≥3MMD to <3MMD, a better understanding of these factors is essential to improve implementation of DSD as a key model for HIV service delivery.…”
Section: Introductionmentioning
confidence: 99%